Historias de dos desgraciadas. Estereotipos de la culpa en la literatura popular española de los siglos XVIII y XIX - Alison Sinclair (Cuadernos de Ilustración y Romanticismo, 2017)
This article contrasts the cases of two women blamed for wrongdoing, and classified as «desgraciadas»: the rape victim, Rosaura de Trujillo and Teresa, the maid who suffers divine punishment for her failure to be charitable to the poor. The examples come from pliegos sueltos, a form of popular literature in Spain, and come from the eighteenth century, with numerous nineteenth-century reprints. By falling outside the boundaries of what is culturally and morally acceptable, each of these women reaffirms those boundaries. In terms of how we interpret them, however, each reveals the complexities of the position of woman as represented in this popular literature. While they are suggestive about the cultural norms of the original date of composition, these cases also have certain generalities that suggest the reasons for their continued popularity.